REKRUTMEN POLITIK PARTAI NASDEM DALAM PEMILIHAN UMUM 2024 DI KABUPATEN KUDUS - Roudhlotul Jannah; Ngabiyanto; Sunarto; Natal Kristiono; Noorochmat Isdaryanto (Universitas Negeri Semarang, 2026)
This study examines the implementation of political recruitment in the Nasdem Party in the 2024 General Election in Kudus Regency. The purpose of this study is to find out about political recruitment and the advantages and disadvantages of political recruitment patterns in the Nasdem Party in the 2024 General Election in Kudus Regency. This research uses a qualitative method. Data sources used primary and secondary sources with data collection techniques through interviews and documentation. The validity technique uses source triangulation techniques. Data analysis through data reduction, data presentation, and conclusion drawing. The results showed that the DPD Nasdem Party organized political recruitment in the form of recruitment of Nasdem Party members or cadres, recruitment of legislative candidates, and recruitment of candidates for regents and deputy regents. Political recruitment in the DPD Nasdem Party of Kudus Regency is carried out with an open system using a selection system through cooption, and is carried out using a lateral pattern. The advantages of political recruitment patterns in the DPD Nasdem Party of Kudus Regency are (1) Open Political Recruitment System, (2) No Dowry Politics, and (3) DPD Nasdem Party of Kudus Regency helps in completing the administrative requirements for legislative candidates. The weaknesses of the political recruitment pattern in the DPD Nasdem Party of Kudus Regency are (1) Candidates for legislative members do not understand the procedures for completing administrative requirements and (2) Candidates for legislative members easily resign.